Sex corrective technologies on the intersex - Mohd Badrul, Mohd Afif; Haneef, Sayed Sikandar Shah; Awang, Abdul Bari (IIUM Press, International Islamic University Malaysia, 2017)
This book is concerned with the gender classical definition of the person with ambiguous genitalia that does not fit into typical male or female category known as hermaphrodite or intersex. It also compares the Islamic position with that of medical science. It uses a qualitative method of articulating the above and examines as to how medicine can manage such a condition. It finds that Islamic countries, including Malaysia, depend on fatwÉs since they do not have a formal Islamic guideline at the time of this study. The bigger problem in medical practice is that it encourages medical intervention at infancy which may not fix the sex of such an infant when he/she attains puberty. Therefore, this book proposes that a medical guideline based on an Islamic framework can be helpful in dealing with this phenomenon.